2019
DOI: 10.3390/toxics7030048
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Lead Exposure from Transport Stations to Human Health: A Case Study in the Highland Province of Vietnam

Abstract: Lead (Pb) is a heavy metal that negatively affects human health. Many studies have shown the relationship between lead exposure and various human activities, of which automobile service stations with gasoline emissions are considered the main cause. However, a limited number of studies have specifically considered lead exposure from automobile stations in Vietnam, as well as its impact on human activities and the surrounding natural resources. The objective of this study was to assess the possible risks of lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In a nationwide survey of agricultural soils, Pb levels surpassed 1.5% of the standard limits set by the Chinese Ministry of Environmental Protection 9 . Le et al 10 reported a similar concern, noting that vegetable samples in the vicinity of a bus station exceeded the permitted limit for Pb contamination in Vietnam. In a separate investigation in Bangladesh 11 , Islam et al found elevated concentrations of Pb, along with Cd, As, Cr, and Ni, in food near industrial zones, surpassing the permitted standards.…”
Section: Introductionmentioning
confidence: 88%
“…In a nationwide survey of agricultural soils, Pb levels surpassed 1.5% of the standard limits set by the Chinese Ministry of Environmental Protection 9 . Le et al 10 reported a similar concern, noting that vegetable samples in the vicinity of a bus station exceeded the permitted limit for Pb contamination in Vietnam. In a separate investigation in Bangladesh 11 , Islam et al found elevated concentrations of Pb, along with Cd, As, Cr, and Ni, in food near industrial zones, surpassing the permitted standards.…”
Section: Introductionmentioning
confidence: 88%
“…Sample analysis. The content of heavy metals in all digested samples were analysed using an atomic absorption spectrophotometer (AAS VGB 210 System) [10]. The instrument settings and operational conditions were set in accordance with the manufacturer's specifications.…”
Section: Methodsmentioning
confidence: 99%
“…9 Gasoline emissions are considered currently the most significant source of lead exposure. 10 The present communication describes a 65-year-old gentleman who worked as a professional gasoline truck driver for 25 years, who, after documented poisoning by benzene and lead, received sequential treatment with first eltrombopag and then romiplostim. The unsuccessful response to eltrombopag, prompted a trial with romiplostim, which resulted in normalization of platelet counts within 4 weeks of treatment.…”
mentioning
confidence: 99%